Perception of Faculties Towards the Implementation of Curriculum in the Semester System of Constituent Campuses of TU - G.C., Krishna Bahadur (Pragyaratna प्रज्ञारत्न, 2024)
Curriculum of any programme indicates its clear objectives, content, learning strategy and the evaluation process. Semester system implies the short term based holistic academic procedures twice in a year. Curricular implementation is the crown of the semester system which reflects the efficiency of teachers, achievement of students and the quality of the programme. To explore the perception of faculties to the implementation of curriculum in the semester system of the constituent college of TU is the leading objectives of this study which provides the guidelines to explore the essential components of the curriculum of the semester system. Literature and the theoretical review of this study has supported to justify the generating information through the field. The qualitative design implies participatory action research paradigm and purposive sampling procedures to select the colleges and the teachers as curriculum implementers. Containing focused on the content coverage, use of teaching and learning strategy, available and use of resources and materials and evaluation process, the information was generated. There is better content coverage of the course and clarity of the objectives in the curriculum whether the techniques of instruction are student centered and the resources and materials are partially available and used to achieved the pre-determined aims. The internal evaluation process is partially flexible but the final examination system is rigid in the semester system of the constituent colleges of TU. For the holistic improvement of the semester system and its sustainability, teacher should be autonomous to prepare the curriculum and its implementation.